Analysis of The Effect of Training, Job Satisfaction, and Work Stress on The Performance of Frontliner Employees at PT Bank Central Asia, Tbk Asia Medan Branch - Vivian, Vivian; Simbolon, Sahat; Sihombing, Nikous Soter; Bhastary, Manda Dwipayani (Enrichment : Journal of Management, 2025)
This study aims to examine the influence of training, job satisfaction, and work stress on the performance of frontliner employees at PT Bank Central Asia Tbk, Asia Medan Branch, both partially and simultaneously. The population in this study consists of 74 people. The sampling technique used was saturated sampling with a total of 74 respondents. Data were collected through questionnaires, employing a quantitative approach and analyzed using SPSS. Validity testing was conducted with Pearson Correlation > 0,30, and reliability testing used Cronbach’s Alpha > 0.60. The results indicate that all research instruments are valid and reliable. The findings reveal that both partially and simultaneously, training, job satisfaction, and work stress have a positive and significant effect on employee performance. Training was proven to enhance employees’ abilities, skills, and understanding in carrying out their tasks, thereby contributing positively to performance improvement. Job satisfaction also plays an essential role in maintaining employees’ motivation, enthusiasm, and loyalty to the company, which ultimately impacts the quality of frontliner services. Meanwhile, work stress in this study was found to have a positive effect on performance, indicating that a certain level of pressure can encourage employees to work more focused, responsive, and driven to achieve established targets. Overall, the contribution of the three variables to employee performance is 60,10%, while the remaining 39,90% is influenced by other factors outside this study. Therefore, the company is advised to continuously improve the quality of training programs, pay attention to factors that foster job satisfaction, and manage work stress at an appropriate level so that it can serve as a positive driver in enhancing employee performance.